Occupational Safety and Health Risk Analysis on Slitter Machines Using the HIRADC and Job Safety Analysis Method at PT KYI - Amri Haikal; Tarman; Hendi Iskandar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Increasingly tight competition in the manufacturing industry requires an optimal Occupational Safety and Health (OSH) system to prevent workplace accidents. This study aims to identify hazard potentials, assess risk levels, and formulate risk-control recommendations for the operation of the slitter machine at PT KYI. A descriptive qualitative-quantitative approach was applied at the Carton Department of PT KYI, Purwakarta, from September 2025 to January 2026. Primary data were obtained through direct observation, interviews with operators and supervisors, and company documentation, then analyzed using the Hazard Identification, Risk Assessment and Determining Control (HIRADC) method and Job Safety Analysis (JSA) with a likelihood-severity risk matrix. The results identified seven major hazard potentials in cutting, adjustment, and material-handling activities, five of which fall into the high-risk category and two into the moderate category. A 5M cause analysis (man, machine, method, material, environment) revealed the human factor as the most dominant cause. The proposed controls include engineering measures such as machine-guard installation, administrative controls through SOP enforcement and safety briefings, and mandatory, consistent use of personal protective equipment. Implementing these controls is expected to sustainably reduce the level of accident risk on the slitter machine.